The digger wasps of the genus Palmodes Kohl, 1890 in Central Asia (Hymenoptera: Sphecidae: Prionychini) - Danilov, Yuriy N.; Byvaltsev, Alexander M. (Zootaxa, 2020)
All available information about the seven species of the digger wasp genus Palmodes Kohl known from Central Asia is summarized. A lectotype is designated for Sphex minor F. Morawitz, 1890. A new species Palmodes hissaricus Danilov is described and illustrated. Sphex mandarinius F. Smith, 1856 is resurrected from synonymy. The following new synonymy has been established: Palmodes mandarinius (F. Smith, 1856) (= Sphex montanus F. Morawitz, 1889), Palmodes melanarius (Mocsáry, 1883) (= Sphex pusillus Gussakovskij, 1930), Palmodes minor (F. Morawitz, 1890) (= Sphex parvulus Roth in de Beaumont, 1967), Palmodes occitanicus (Lepeletier de Saint Fargeau et Serville, 1828) (= Sphex palmetorum Roth, 1963). An original key to the Palearctic species is provided.